(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the use of storytelling as an effective method in teaching English. It highlights how storytelling engages students, enhances language skills, and fosters creativity. The paper discusses interactive storytelling techniques, such as role-playing, collaborative story creation, and digital storytelling, providing practical examples for classroom application.